Spin crossover in hydrogen-bonded frameworks of FeII complexes with organodisulfonate anions. Issue 24 (28th May 2019) - Shen, Fu-Xing; Pi, Qian; Shi, Le; Shao, Dong; Li, Hong-Qing; Sun, Yu-Chen; Wang, Xin-Yi
Abstract : Four spin crossover Fe II complexes of hydrogen-bonded frameworks were constructed from the charge-assisted hydrogen bonds between the Fe II complexes and organodisulfonate anions. Abstract : We present here the syntheses, crystal structures, and thermal and magnetic properties of a series of mononuclear Fe 2+ spin crossover (SCO) complexes of the formula [Fe(bamp)2 ]·Anion·Solv (Anion = NDS 2−, Solv = 2H2 O, 1NDS ; Anion = BPDS 2−, Solv = 4.4H2 O, 2BPDS ; Anion = ABDS 2−, Solv = Et2 O and H2 O, 3ABDS ; Anion = DNDS 2−, Solv = MeCN, 4DNDS ; bamp = 2, 6-pyridinedimethanamine, H2 NDS = 1, 5-naphthalenedisulphonic acid, H2 BPDS = 4, 4′-biphenyldisulphonic acid, H2 ABDS = 4, 4′-azobenzenedisulfonic acid, H2 DNDS = 4, 4′-dinitrostilbene-2, 2′-disulfonic acid). The structures and SCO properties of these complexes can be finely modified by organodisulfonate couteranions. Single-crystal X-ray analyses revealed that all these compounds are hydrogen-bonded three-dimensional frameworks constructed from the charge-assisted hydrogen bonds between bamp donors, organodisulfonate acceptors, and/or crystallized solvent molecules. SCO behavior was observed in all four complexes and has been evidenced by detailed structural and magnetic investigations. While1NDS exhibits a sharp cooperative SCO transition with a transition temperature T 1/2 of 247 K, 2BPDS, 3ABDS, and4DNDS undergo more gradual SCO transitions with T 1/2 values of 176, 171 and 158 K, respectively. Magneto-structural relationship studies revealed that the tunable SCO properties, including the trend of the transition temperatures and the cooperativity of the SCO transition, are mainly attributable to the size of the organodisulfonate anions. This study shows that in order to exhibit cooperative SCO properties, "efficient" hydrogen bonds directly connecting the SCO centers, rather than those between the SCO centers and the innocent neighboring groups, are preferred.